1998
DOI: 10.1002/(sici)1097-0290(19980720)59:2<171::aid-bit5>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective hydroxylation of 4‐alkylphenols by vanillyl alcohol oxidase

Abstract: Abstract:Vanillyl alcohol oxidase (VAO) from Penicillium simplicissimum catalyzes the enantioselective hydroxylation of 4-ethylphenol, 4-propylphenol, and 2-methoxy-4-propylphenol into 1-(4Ј-hydroxyphenyl)ethanol, 1-(4Ј-hydroxyphenyl)propanol, and 1-(4Ј-hydroxy-3Ј-methoxyphenyl)propanol, respectively, with an ee of 94% for the R enantiomer. The stereochemical outcome of the reactions was established by comparing the chiral GC retention times of the products to those of chiral alcohols obtained by the action of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0
1

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 18 publications
1
38
0
1
Order By: Relevance
“…VAO and PCMH have a similar substrate specificity (6,13,14), and the active site architecture of both enzymes is highly conserved (4,8). However, VAO preferentially converts 4-ethylphenol and 4-propylphenol to the corresponding (R)-1-(4Ј-hydroxyphenyl)alcohols (14), whereas PCMH favors the production of the (S)-enantiomers (15,16).…”
supporting
confidence: 62%
“…VAO and PCMH have a similar substrate specificity (6,13,14), and the active site architecture of both enzymes is highly conserved (4,8). However, VAO preferentially converts 4-ethylphenol and 4-propylphenol to the corresponding (R)-1-(4Ј-hydroxyphenyl)alcohols (14), whereas PCMH favors the production of the (S)-enantiomers (15,16).…”
supporting
confidence: 62%
“…tion is limiting the rate of overall catalysis. Vanillyl-alcohol oxidase converts both 4-ethylphenol and 4-propylphenol to a mixture of the corresponding benzylic alcohol and alkenylic phenol in a ratio of approximately 4 :1 [15]. gesting that the rate of enzyme reduction is partially limiting the HPLC product analysis revealed that deuteration of CA has no rate of overall catalysis.…”
Section: Synthesis Of 4-[b-2 H 3 ]Methylphenolmentioning
confidence: 99%
“…Furthermore, the extent of reduction also decreased indicating formed at pH 9.4. These results suggest that in the second relatively slow phase of the reductive half-reactions of vanillyl-alcothat the rate of reduction (k 2 ) decreased to a greater extent than vinylic phenols are formed [15]. It is not clear whether this competing rearrangement of the 4-alkylphenol p-quinone methide intermediates is related to the water accessibility of the active site.…”
Section: Synthesis Of 4-[b-2 H 3 ]Methylphenolmentioning
confidence: 99%
See 2 more Smart Citations